The regulation mechanisms of soluble starch and glycerol for production of azaphilone pigments in Monascus purpureus FAFU618 as revealed by comparative proteomic and transcriptional analyses. (April 2018) - Huang, Zi-Rui; Zhou, Wen-Bin; Yang, Xue-Ling; Tong, Ai-Jun; Hong, Jia-Li; Guo, Wei-Ling; Li, Tian-Tian; Jia, Rui-Bo; Pan, Yu-Yang; Lin, Jun; Lv, Xu-Cong; Liu, Bin
Abstract: Monascus spp. have been used for thousands of years as a traditional food additive in China. This mold can produce many different types of commercially valuable secondary metabolites of biological activity. Soluble starch and glycerol are the two principal carbon sources universally utilized by Monascus for the production of beneficial metabolites. In this study, the effects and regulation mechanisms of soluble starch and glycerol for M. purpureus FAFU618 on Monascus azaphilone pigments (MonAzPs) were investigated through ultra-performance liquid chromatography quadrupole time of flight mass spectrometry (UPLC-QTOF-MS/MS), comparative proteomics and quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR). The production of intracellular and extracellular pigments was significantly different between the soluble starch group (SSG) and glycerol group (GCG). Additionally, the components of intracellular pigments revealed by UPLC-QTOF-MS/MS showed that Monascin and Ankaflavin increased significantly in the GCG, while Rubropunctatin and Monascorubrin increased in the SSG. Differentially expressed proteins of mycelia between SSG and GCG were analyzed by two-dimensional gel electrophoresis (2-DE) and MALDI-TOF/TOF MS. We identified 27 proteins with statistically altered expression, of which 18 proteins associated with the EMP (glycolytic pathway), translation, energy generation, proteolysis, etc. were up-regulated, and 9 proteins, including ribosomal proteins, heat shock proteins (HSPs) and others, were down-regulated in GCG. Meanwhile, the expression levels of MonAzP biosynthetic genes were also analyzed by RT-qPCR, and the results showed that mppA, mppC, mppR1 and mppR2 were down-regulated, whereas genes MpPKS5, MpFasA2, MpFasB2, mppB, mppD and mppE were up-regulated. Collectively, these findings illustrate that the regulation of MonAzPs is not only closely related to the expression levels of certain proteins in the polyketide synthesis pathway but also closely related to the concentration of primary metabolism-generated molecules that are used as substrates for polyketide synthesis. The present study provides insights into the regulation of different carbon sources on the metabolism of MonAzPs in M. purpureus FAFU618. These results may promote further development of functional foods or medicines from Monascus spp. fermented products. Graphical abstract: Unlabelled Image Highlights: Effects of glycerol and soluble starch for the production and components of Monascus azaphilone pigments were investigated. Glycerol can change the components of the intracellular pigments and promote yellow pigment accumulation. Monascin and Ankaflavin were increased significantly when glycerol was used as the sole carbon source. Regulation mechanisms of glycerol were revealed by comparative proteomics and RT-qPCR.